2003
DOI: 10.1016/s0002-9440(10)63547-x
|View full text |Cite
|
Sign up to set email alerts
|

The Myofibroblast Is the Predominant Plasminogen Activator Inhibitor-1-Expressing Cell Type in Human Breast Carcinomas

Abstract: The tumor level of plasminogen activator inhibitor-1 (PAI-1) is an informative biochemical marker of a poor prognosis in several cancer types. However, the tumor biological functions of PAI-1 and the identity of PAI-1-expressing cells are controversial. With the aim of immunohistochemically localizing PAI-1 in formalin-fixed, paraffin-embedded invasive ductal breast carcinoma samples, we raised new polyclonal antibodies against PAI-1 from different expression systems. The antibodies were affinity purified by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 54 publications
4
77
0
1
Order By: Relevance
“…Immunohistochemical localization studies of proteins involved in the activation and regulation of the efficient serine protease plasminogen, including urokinase plasminogen activator (uPA) and its specific inhibitor PAI-1 show that both are mainly expressed by myofibroblasts in human breast cancer. 45,46 High levels of uPA and PAI-1 are strongly correlated with poor prognosis in breast cancer, 47,48 supporting the assumption that the myofibroblast express a promoting role in cancer invasion. We recently reported that the predominant PAI-1 expressing cell in human colorectal cancer also is the myofibroblast, 49 and earlier studies indicated that elevated levels of PAI-1 in colon cancer patients are associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 94%
“…Immunohistochemical localization studies of proteins involved in the activation and regulation of the efficient serine protease plasminogen, including urokinase plasminogen activator (uPA) and its specific inhibitor PAI-1 show that both are mainly expressed by myofibroblasts in human breast cancer. 45,46 High levels of uPA and PAI-1 are strongly correlated with poor prognosis in breast cancer, 47,48 supporting the assumption that the myofibroblast express a promoting role in cancer invasion. We recently reported that the predominant PAI-1 expressing cell in human colorectal cancer also is the myofibroblast, 49 and earlier studies indicated that elevated levels of PAI-1 in colon cancer patients are associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 94%
“…Intriguingly, several studies have confirmed that PAI-1 was an important factor during the transformation of fibroblasts to myofibroblasts, which amplified the inflammatory response and resulted in the progression of fibrosis [13][14][15] . Offersen et al observed that myofibroblasts were the predominant PAI-1-expressing cell in breast carcinomas based on immunohistochemistry double staining [16] . Another study showed that the crucial step was the cleavage of the uPA receptor to D2D3 after binding of PAI-1 to uPA and the uPA receptor during fibroblast-to-myofibroblast differentiation [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal anti-PAI-1 antibodies (mAbs) were described previously: mAb-1 (Nielsen et al, 1986;Bødker et al, 2003); mAb-2 (Wind et al, 2001);mAb-5 (Munch et al, 1991);mAb-6 (Wind et al, 2001);mAb-7 (Gils et al, 2003); MA33B8 (Verhamme et al, 1999;Gorlatova et al, 2003;Naessens et al, 2003); MAH4B3 (Declerck et al, 1995;Gils et al, 2003). A preparation of rabbit polyclonal anti-PAI-1 antibodies was described previously (Offersen et al, 2003). A horseradish peroxidase (HRP)-conjugated monoclonal anti-M13 phage antibody was purchased from GE Healthcare (Chalfont St. Giles, Buckinghamshire, UK).…”
Section: Methodsmentioning
confidence: 99%